PROFILE OF SUCCESSFUL ENGLISH LANGUAGE LEARNERS - Muslimin, Afif Ikhwanul (English Education: Jurnal Tadris Bahasa Inggris, 2018)
English is one important skills to be acquired by the students for achieving a prospective job with a good salary. Hence, the appropriate learning strategies to be successful English language learners are essential to boost the learning achievement. The facts, some UIN Mataram English I students have depicted themselves as successful English language learners. Furthermore, this present study is a descriptive qualitative case study involving ten students of S1 Islamic Elementary School Teachers Science (PGMI) Departments students at the UIN Mataram who were in academic year 2016-2017 and passed English I program. The subjects was chosen on the basis of their English achievement and their language capability. The subjects had good scores for the English subject and they also had excellent language achievement proven by being winner of some English contest such as debate competition, speech contest, English business meeting presentation, and TOEFL score. The data will be collected through observation, questionnaire responses, and interviews. The study found that the successful language learners are overall, taking responsibility for their learning, self-initiating and well motivated, and initiating learning opportunities for themselves. They also did a lot of independent learning activities which suit their interest. From the six learning strategies employed by those learners, namely, memorizing strategy, affective strategy and social strategy, cognitive strategy, compensation strategy, metacognitive strategy, it seems that those belonging to direct strategies are all used since the strategies help students directly.Keywords: Successful language learners, profile, language learning strategies